Penyuluhan Siswa Pola Hidup Bersih dan Sehat “Membangun Kebiasaan Sehat: Menjaga Kebersihan dan Kesehatan” - Sobirin, Moch. Sahril; Husni, Muhammad (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Clean and healthy lifestyle (PHBS) is an important element in disease prevention and improving quality of life, but it is often not understood and applied optimally, especially among elementary school students. This study aims to evaluate the effectiveness of PHBS education counseling in building healthy habits among elementary school students and determine the most effective method in delivering educational materials. The method used in this study was a pre-test and post-test design involving 7,8,9 th grade students of MTs Al Khoiriyah. Extension activities included interactive presentations, hands-on practice sessions, and educational activities such as games and discussions. Evaluation was conducted through quizzes and surveys before and after counseling to measure changes in students' knowledge and practices related to PHBS. The results showed a significant increase in students' knowledge and practices regarding healthy habits after attending the counseling. Students showed a better understanding of personal hygiene techniques, consumption of nutritious food, and other healthy habits. Interactive educational activities proved to be highly effective in increasing student engagement and information retention.